2019
DOI: 10.1177/1177932219896538
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Selected Terpenoids From Dalbergia sissoo With Catalytic Domain of Matrix Metalloproteinase-1: An In Silico Assessment of Their Anti-wrinkling Potential

Abstract: Matrix metalloproteinase-1 (MMP-1) is a predominant collagenase enzyme that cleaves collagen fibers, contributing to skin wrinkling. Matrix metalloproteinase-1 inhibitors of herbal origin may provide an earnest probability to offer a novel curative approach against MMP-1-mediated collagenolysis, prompted by ultraviolet (UV)-induced overexpression of MMP-1. In this in silico study, we have explored the MMP-1 inhibitory potential of selected terpenoids from Dalbergia sissoo extracts. Two triterpenoids (lupeol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Another study by Yasmeen et. al displayed that phytol showed a binding affinity of -7.06 kcal/mol with second highest drug score and could be a potent inhibitory drug for MMP-1 along with potentially safe to be developed into active pharmaceutical drug against MMP-1 [10].…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Yasmeen et. al displayed that phytol showed a binding affinity of -7.06 kcal/mol with second highest drug score and could be a potent inhibitory drug for MMP-1 along with potentially safe to be developed into active pharmaceutical drug against MMP-1 [10].…”
Section: Resultsmentioning
confidence: 99%
“…In It also exhibited antioxidant, anti-inflammatory, antimicrobial, cytotoxic, and immune-modulating activities [ 53 ]. Previous molecular docking studies revealed that phytol can bind to amino acid residues in the catalytic domain of MMP-1 (collagenase enzyme), with binding energy (−7.06 kcal/mol) comparable to that (−8.05 kcal/mol) of the reference compound doxycycline [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…7 ), meaning it could still be considered to have good potential as an oral drug as a drug candidate is usually described as having low appropriateness as an oral medication if it does not meet multiple standards. 33 This theoretical information could then be used as initial data for experimental testing considerations.…”
Section: Resultsmentioning
confidence: 99%